REVIVING THE ALPINE IBEX: ADDRESSING GENETIC AND HEALTH CONCERNS OF SLOVENIAN IBEX WITH BROADER IMPLICATIONS IN BIODIVERSITY - Simon Horvat (Slovenian Veterinary Research, 2023)
This issue’s cover illustration depicting the Alpine ibex against the backdrop of iconic Slovenia's Triglav mountain is inspired by the manuscript by Bužan et al. and serves as a poignant reminder of a lost legacy and biodiversity due to greed and overhunting. These magnificent creatures thrived entire European Alpine region before their extermination in the 19th century, with the only surviving wild population of Alpine ibex in the Gran Paradiso National Park (then a royal hunting reserve) in Italy. Reintroduction initiatives from this small population have since rebounded ibex to tens of thousands across the Alpine region. However, as the article on the Slovenian population of Alpine ibex by Bužan et al. in this issue clearly shows, while current numbers seem more promising, the genetic bottleneck they experienced from this near-extinction event has left lasting impacts on their genetic diversity.